Carnitine Protects against MPP+-Induced Neurotoxicity and Inflammation by Promoting Primary Ciliogenesis in SH-SY5Y Cells - Ji-Eun Bae; Joon Bum Kim; Doo Sin Jo; Na Yeon Park; Yong Hwan Kim; Ha Jung Lee; Seong Hyun Kim; So Hyun Kim; Mikyung Son; Pansoo Kim; Hong-Yeoul Ryu; Won Ha Lee; et al. (Cells, 2022)
Primary cilia help to maintain cellular homeostasis by sensing conditions in the extracellular environment, including growth factors, nutrients, and hormones that are involved in various signaling pathways. Recently, we have shown that enhanced primary ciliogenesis in dopamine neurons promotes neuronal survival in a Parkinson’s disease model. Moreover, we performed fecal metabolite screening in order to identify several candidates for improving primary ciliogenesis, including L-carnitine and acetyl-L-carnitine. However, the role of carnitine in primary ciliogenesis has remained unclear. In addition, the relationship between primary cilia and neurodegenerative diseases has remained unclear. In this study, we have evaluated the effects of carnitine on primary ciliogenesis in 1-methyl-4-phenylpyridinium ion (MPP+)-treated cells. We found that both L-carnitine and acetyl-L-carnitine promoted primary ciliogenesis in SH-SY5Y cells. In addition, the enhancement of ciliogenesis by carnitine suppressed MPP+-induced mitochondrial reactive oxygen species overproduction and mitochondrial fragmentation in SH-SY5Y cells. Moreover, carnitine inhibited the production of pro-inflammatory cytokines in MPP+-treated SH-SY5Y cells. Taken together, our findings suggest that enhanced ciliogenesis regulates MPP+-induced neurotoxicity and inflammation.